PEMBUATAN PRODUK MULTIMEDIA DAN STRATEGI PROMOSI MELALUI MEDIA DIGITAL PADA WARUNG MISO MEDAN - Alicia, Angelina; Laulita, Nasar Buntu (Transpublika Publisher, 2022)
The rapid development of digital technology and social media has had a huge impact on the business world, including medium-sized businesses. The strategy for trade promotion through digital media and multimedia products is more prospective because it attracts potential customers to obtain information about products being sold and transactions via the internet. So far, the partner namely Warung Miso Medan requires buyers to come directly to the location or order via WhatsApp. The purpose of this activity is to accompany and provide training to Warung Miso Medan on promotional strategies through digital media. The stages of the activity are: (1) Introduction to social media (2) Introduction to marketplace (3) Documentation of multimedia products (4) Receiving orders and sending (5) Designing banners. The results of Community Service activities are partners who have social media, are registered on the marketplace, and have an understanding of promotion strategies through social media and are able to manage them.